Fear of Missing Out Predicts Distraction by Social Reward Signals Displayed on a Smartphone in Difficult Driving Situations - Matias, Jérémy; Quinton, Jean-Charles; Colomb, Michèle; Normand, Alice; Izaute, Marie; Silvert, Laetitia (Frontiers in Psychology, 2021)
Smartphones are particularly susceptible to elicit driver distraction and impair road safety. Recent selective attention models lead to expect that smartphones might be effective in capturing attention due to their social reward history. In this context, individual differences in terms of Fear of Missing Out (FoMO) – describing the apprehension of missing out on socially rewarding experience – should play an important role. Interestingly, this factor has already been associated with self-reported estimations of a greater attention paid to smartphones while driving. However, the potential link between FoMO and smartphone-induced distraction has never been tested experimentally. To fill this gap, we conducted a preliminary study to investigate whether FoMO would modulate attentional capture by reward distractors displayed on a smartphone. Neutral stimuli were first associated with high or low social reward outcomes through a classical visual search task. In a second phase, those social reward stimuli were displayed as distractors on a smartphone' screen while participants performed a visual search task of a pedestrian or a roe deer in driving scenes. Importantly, results showed a significant three-way interaction between FoMO, social reward distraction and the task difficulty (i.e., various fog density). More precisely, individual FoMO scores predicted attentional capture by irrelevant social reward distractors, with longer reaction times observed when a high social reward was present (compared to lower rewards) under attentional-demanding conditions (i.e., high-fog density). These results highlight the importance to consider FoMO when investigating smartphone-based distraction. Limitations are discussed and future research directions regarding driver distraction are provided.